Bone Morphogenetic Proteins: Systems Biology Regulators - Vukicevic, Slobodan; Sampath, Kuber T. (Springer International Publishing : Imprint: Springer, 2017)
This book focuses on the salient features of the biology of Bone Morphogenetic Proteins and the advances in our understanding of their structure and function and of downstream signaling, as well as their governance in systems biology from bone and dentin to kidney, cancer, diabetes, iron homeostasis and angiogenesis, including rare musculoskeletal disorders. BMPs, also referred to as growth and differentiation factors, are members of the TGF-beta superfamily and are highly conserved from fruit flies to mammals and are responsible for the formation of practically every organ during embryo development and involved in adult tissue injury and repair. BMPs establish their extracellular gradient by interacting with their respective antagonists and regulate their function through SMAD-dependent down-stream signaling effector genes. This volume is aimed at scientists and professionals dealing with metabolic disorders, nutrition, systems biology diseases, rare musculoskeletal conditions, and disorders related to iron metabolism, including anemia of chronic disease, hereditary hemochromatosis and beta thalassemia.
Keywords: Medicine.; Immunology.; Proteins.; Cytokines.; Growth factors.; Systems biology.; Cell biology.; elektronické knihy; electronic books